2022
DOI: 10.1186/s12974-022-02491-1
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Nrf2 expression protects spinal cord from oxidative stress following spinal cord injury in a male mouse model

Abstract: Background Spinal cord injury (SCI) induces a multitude of deleterious processes, including neuroinflammation and oxidative stress (OS) which contributed to neuronal damage and demyelination. Recent studies have suggested that increased formation of reactive oxygen species (ROS) and the consequent OS are critical events associated with SCI. However, there is still little information regarding the impact of these events on SCI. Astrocytes are key regulators of oxidative homeostasis in the CNS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…Recently, it has been found that Nrf2 is a major transcriptional regulator of cellular antioxidant stress response in astrocytes; its regulation of antioxidant system plays a key role in the early stage after spinal cord injury. Increased Nrf2 activity in astrocytes can improve the inflammatory response after spinal cord injury and promote the recovery of motor function [ 38 ].…”
Section: Pathophysiological Changes Of Scimentioning
confidence: 99%
“…Recently, it has been found that Nrf2 is a major transcriptional regulator of cellular antioxidant stress response in astrocytes; its regulation of antioxidant system plays a key role in the early stage after spinal cord injury. Increased Nrf2 activity in astrocytes can improve the inflammatory response after spinal cord injury and promote the recovery of motor function [ 38 ].…”
Section: Pathophysiological Changes Of Scimentioning
confidence: 99%
“…The results of GO biological processes and KEGG pathways of hub genes were in line with many previous studies. Inflammation, oxidative stress, IL-17 signaling pathway, and so on were regarded as indispensable parts of specific mechanisms in SCI [43][44][45]. There are 93 molecules involved in IL-17 family signaling events in the IL-17 signaling pathway resource [46].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that activation of Nrf2 in astrocytes can protect themselves and neighboring cells, including neurons, from oxidative damage in the injured or diseased brains and spinal cords, thereby improving their pathological conditions (Draheim et al, 2016; Sigfridsson et al, 2018; Vargas et al, 2008; Zhao et al, 2022). In the injured brains, hemin, released from hemoglobin during hemorrhage at these injury sites, is thought to elicit iron‐mediated cellular damage, leading to the dysfunction of BBB (Imai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%